Misunderstandings of Feminism Among Women in Patriarchal Societies - Muhammad Yazid Zidan; Muhammad Satrio Adhi Wicaksono; Ika Arinia Indriyany (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Gender inequality remains an ongoing issue within Indonesiaâ€™s social dynamics. Although various policies have been introduced to strengthen the principle of equality between men and women, unequal gender relations can still be observed in both domestic and public spheres. In this context, feminism, which seeks to challenge gender inequality, is often misunderstood as a movement that opposes men or as an ideology that contradicts cultural values and social norms. This study aims to examine how feminism is perceived within Indonesian society and how patriarchal culture contributes to maintaining such misconceptions. This research employs a qualitative approach using a literature study method based on academic journals, scholarly books, and official publications related to feminism and patriarchy. The theoretical framework applied in this study is Judith Butlerâ€™s post-structuralist feminism, which emphasizes that gender identity is socially constructed through the repeated performance of cultural norms. The findings indicate that misconceptions about feminism are not only influenced by limited gender literacy but also by the internalization of patriarchal values that have long been normalized within social life. These values are reproduced through family structures, educational institutions, media representations, and cultural practices that shape the image of the â€œideal woman.â€ Therefore, a more contextual understanding of feminism is necessary to foster a more constructive discussion on gender equality in Indonesian society.